MANAJEMEN PERSEDIAAN BAHAN BAKU KERIPIK PISANG DI INDUSTRI “FLAMBOYAN” KELURAHAN PANAU KECAMATAN TAWAELI KOTA PALU - Erikayanti, Agustin Dwi; Laapo, Alimuddin; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
This research aims to know the amount of the purchase of raw materials is the most economical and knowing the exact time of booking back in the industry